Effects of pulse-like earthquake motions on a typical subway station structure obtained in shaking-table tests. (1st November 2019) - Chen, Z.Y.; Liu, Z.Q.
Highlights: Large-scale shaking-table tests were carried out for a subway station structure. Effects of velocity-pulse parameters on structural responses were studied. Velocity pulse increases the amplitude of soil first-mode shear-type deformation. Multiple pulse cycles may trigger remarkable resonance-like phenomena. Abstract: A series of large-scale shaking table tests on a typical subway station structure were carried out for pulse-like earthquake motions. The propagation of earthquake motions in soils is explored. The effects of velocity pulse parameters (i.e., pulse shape, pulse frequency ( fp ), and pulse duration ( Tpd )) on dynamic responses of the structure are analyzed from the viewpoint of the dynamic characteristics of soils. It is found that the site amplifies the frequency components of dynamic excitation in specific frequency bands (i.e., the amplification frequency band, AFB). With an increase in earthquake motion intensity, the AFB gradually moves towards low frequencies. Additionally, the bandwidth gradually narrows. The velocity pulse increases the amplitude of the first-mode shear deformation of soils and thus the seismic internal force response of underground structures. In addition, the effect of a one-sided pulse in terms of increasing the first-order shear deformation amplitude of soil is more pronounced than the effect of a two-sided pulse. Pulse-like earthquake motions with long pulse duration and multiple pulse cycles may trigger remarkable resonance-like phenomena of soils and further aggravate soil and structure responses when the main pulse frequencies are located in the AFB of soils.